(3MGTjI CHh TMeI Ydi MGTjI GdSjO Ydi TQM GdbWH Ydi GdTSjIs - (3CHh TMeIs ((3ESMGb Hf YHO Gddg Hf jYbhHs)
(3ChdgG (B:s
(3HSe Gddg bhdg aj cKjQ ef GdfSN jQjO Cf hLhg daXg KdGK aj cKjQ ef GdfSN hEf cGf ehgeG dhbhYgG ef GdeUfa dcf GdUhGH HNdGag ahdg hbYJ SghG ef bde GdfGSN jYfj def jgPg GddaXI de jbY ef GdeUfa Hd COQLgG GdfGSNhf aj GdeJf SghG s
(3BNQgG (B:s
... (3bhdg hgPG CXgQ aSGOG dGTJeGdg Ydi GdaSGO GdSGHb hYdi RjGOI CeG GdaSGO GdSGHb aXf hCeG GdRjGOI aHWdGf GdeOdhd CjVG dGf GdfSHI djSJ HLRA aj GdJUOjb hEfeG GdLRA JUhQg ceG dG jNai JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2\1063s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdadSaI hGdefWbs